Oral clioquinol is effective in the treatment of a fly model of Candida systemic infection. - Pippi, B.; Merkel, S.; Staudt, K.J.; Teixeira, M.L.; de Araújo, B.V.; Zanette, R.A.; Andrade, S.F.; Fuentefria, A.M. (Mycoses, 2019)
Clioquinol was used in the 1950s-1970s as antimicrobial but its oral formulations were withdrawn from the market due to suspected neurotoxicity. Currently, there is possibility of repositioning of oral clioquinol formulations. To evaluate the antifungal activity and toxicological parameters of clioquinol and the other two 8-hydroxyquinoline derivatives using alternative animal models and to study the interaction dynamic of clioquinol with Candida albicans. We used Toll-deficient Drosophila melanogaster to test the protective effect of 8-hydroxyquinolines against C. albicans infection. Toxicological parameters were investigated in chicken embryo. A mathematical model-based analysis of the time-kill data of clioquinol was performed to obtain pharmacodynamic characteristics. Clioquinol fully protected D. melanogaster from the infection. The 8-hydroxyquinolines did not cause changes in opening of the beak and movement of the chicken embryo; however, clioquinol and compound 2 increased arterial pulsation. Compound 3 was lethal at 1 mg mL-1 . Effective concentration found in modelling indicated that clioquinol was highly effective against C. albicans (0.306 ?g mL-1 ) in easily achievable serum levels; clioquinol rapidly achieved kill rate reaching the maximum effect after 13 hours. These results support the potential of clioquinol to be used as a systemic antifungal agent.